Characteristics of Anorectal Malformations in Children at the United States-Mexico Border: A 3-Year Study. Issue 1 (July 2020) - Rosas-Blum, Eduardo D.; Reddy, Ajay; Shaban, Mohamed A.; Aziz, Sandra; Do, Ailinh; Spurbeck, William; Francis, Denease
ABSTRACT: Background: Anorectal malformations (ARMs) are a group of congenital malformations affecting the lower gastrointestinal, urogenital, and/or gynecological systems. They occur in approximately 1 in 5000 live births, with a slight male predominance. ARMs can appear in isolation or in association with other anomalies. The literature contains little information about the characteristics of ARMs in United States Hispanic populations. Methods: An institutional review board–approved chart review was conducted in all patients with ARMs seen at a single institution in El Paso, Texas, from January 2012 to December 2015. Data regarding demographics, types of ARMs, associated syndromes, and long-term complications were recorded using the Krickenbeck classification system. Results: Of the 37 patients included in the study, 20 were boys and 17 were girls. The most common ARMs were rectoperineal fistula (46%), rectourethral fistula, and cloacal malformation. Constipation was the most common long-term complication, especially in patients with recto-perineal fistula. Conclusion: Children in the Borderland community may have a higher percentage of recto-perineal fistula than previously reported. Postoperative complications in Hispanic children with ARM were comparable to those reported in other populations.